2017
DOI: 10.1007/s00420-017-1239-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cooperation between general practitioners, occupational health and rehabilitation physicians in Germany: a qualitative study

Abstract: PurposeTo achieve successful medical rehabilitation and timely return to work, general practitioners, occupational health and rehabilitation physicians need to cooperate effectively. This cooperation, however, can be hampered by organizational, interpersonal, and structural barriers. In this article, we present and discuss suggestions proposed by physicians and patients on how these barriers can be overcome.MethodsWe conducted eight qualitative focus group discussions with general practitioners (GPs), occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Other than in the therapeutic setting with patients and their selected therapist, in the occupational setting employees may tend to withhold relevant health-related data from the company-selected OP. 28 The fact that the observed lifetime prevalence of depression is 11.6% 44 and is almost identical with the OPs’ estimation of the percentage of their employees with depression strengthens the validity of our study.…”
Section: Discussionsupporting
confidence: 80%
“…Other than in the therapeutic setting with patients and their selected therapist, in the occupational setting employees may tend to withhold relevant health-related data from the company-selected OP. 28 The fact that the observed lifetime prevalence of depression is 11.6% 44 and is almost identical with the OPs’ estimation of the percentage of their employees with depression strengthens the validity of our study.…”
Section: Discussionsupporting
confidence: 80%
“…This was highlighted by the extensive use of “we” and “they” in the statements. According SIA, the mere perception of belonging to two distinct groups can be sufficient to provoke intergroup competitive or discriminatory responses on the part of the in-group [ 48 ]. As predicted, the protagonists described a positive perception of their own professional group, while maintaining negative or prejudicial perceptions about other professional groups, especially regarding OPs.…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on an explorative, qualitative research design using the Social Identity Approach (SIA) by Tajfel and Turner [ 50 – 56 ] as the theoretical underpinning, eight focus group discussions (FGDs) for data collection, and qualitative content analysis [ 57 ] for data analysis. A more detailed outline of methods and research questions is provided in the study protocol [ 2 ] and the preceding publications [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stapelfeldt et al (2018) reported that several professionals, e.g., employers, occupational and physical therapists, and social workers, should be involved in interventions to support occupationally active cancer survivors to retain work [31]. As in the Netherlands and other Western countries, the healthcare and occupational health systems are not naturally intertwined, it is challenging to ensure structured coordination of care and greater interdisciplinary collaboration [32].…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%